Protection of intellectual, biological and cultural property in Papua New Guinea - Whimp, Kathy; Busse, Mark (Australian National University E Press, 2013)
Intellectual, biological and cultural property rights are a powerful and debatable topic. They offer the possibility for protection of rights to intangible resources, including the products of knowledge and creativity. The forces of globalisation have made this subject of immediate, international concern. Struggles for ownership of intellectual property occur between and within local and global arenas. This book examines important questions which Papua New Guinea must ask in the development of intellectual property legislation. The chapters are written by specialists in the fields of medicine, law, the environment, music, genetics and traditional cultural knowledge. The wise and creative protection of intellectual, biological and cultural property is important if Papua New Guinea is to successfully define and realise its future. This book is for all those interested in finding the best policies for protecting these rights wherever they may live and work.